Analysis of the relationship of soybean farmers response and income on The Pajale Special Efforts (UPSUS). Issue 1 (April 2020) - Fudjaja, L; Tenriawaru, A N; Mahyuddin,; Saadah,; Darwis,; Diansari, P; Sulili, A; Wirdansyah, A
Abstract: Soybean self-sufficiency has become the government's primary target since 2015 along with two other food commodities, namely rice, and corn. The UPSUS program (Special Efforts) is one of the efforts to support soybean self-sufficiency. Special Efforts (UPSUS) are the main program of the Ministry of Agriculture to improve the welfare of farmers. With the UPSUS, it is expected that soybean production will increase. This study aims to determine the relationship between soybean farmers' responses to farm income. The population of the study was farmers who were involved in the UPSUS Pajale Program as many as 150 people using the purposive sampling method. The data analysis used in this study is Chi-Square analysis. Chi-Square is a statistical test that is used to test hypotheses if the population consists of two or more classes where the data is categorical. The results of the study concluded that there was no relationship between the response to the Pajale Special Effort Program (UPSUS) and the income obtained by farmers.